BMD status of Postmenopausal Women in relation with BMI: A study with 93 cases (Bangladesh Journal of Nuclear Medicine, 2016)
Objectives: Low bone mass is a common disorder in elderly population which predisposes to fracture with minimal trauma. This study was performed to find out the association between the Body Mass Index (BMI) and Bone Mineral Density (BMD) in postmenopausal women.Materials and Methods: This cross sectional study was carried out at Institute of Nuclear Medicine and Allied Sciences Comilla and Mitford, Dhaka over a period of 12 months from January 2013 to December 2013. A total 93 postmenopausal women were enrolled for this study. All postmenopausal women underwent a BMD scan of femoral neck and lumbar vertebrae using a Dual Energy X-ray Absorptiometry (DEXA). Participants were categorized into three groups according to their age and BMI. BMD were expressed base on T-score according to WHO criteria. The relation among BMI, age and BMD were assessed.Results: The results of this study showed that the mean age of the study group was 57.13±7.49 years with range of 46 to 75 years. The most postmenopausal women were in age group 55-65years. The mean BMI of the study subjects were 24.18±5.08 kg/m2 with a range of 15.62 to 36.20 kg/m2. Among 93 subjects osteopenia was greater at lumbar spine (45.2%) with T-score mean±SD-1.83±0.33 and osteoporosis at femoral neck (51.6%) with T-score mean ±SD-3.36±-0.67. Pearsons correlation coefficient test showed inverse relationship between age and BMD both lumbar spine (r = -0.301, p = 0.003) and femoral neck (r = -0.303, p=0.003) whereas the positive relation between BMI and BMD both at lumbar spine (r=0.338, p=0.001) and femoral neck (r =0.343, p=0.001). These showed that with advancing age, BMD decreases and the risk of osteoporosis increases and with increasing BMI, BMD increases and risk of osteoporosis decreases.Conclusion: The findings of this study portrait that aging and low BMI are risk factors associated with bone loss. So preventive measure should be taken for high risk post menopausal women.Bangladesh J. Nuclear Med. 17(2): 138-141, July 2014